Determination of Acid and Neutral Cannabinoids in Extracts of Different Strains of Cannabis sativa Using GC-FID - Ibrahim, Elsayed A.; Gul, Waseem; Gul, Shahbaz W.; Stamper, Brandon J.; Hadad, Ghada M.; Abdel Salam, Randa A.; Ibrahim, Amany K.; Ahmed, Safwat A.; Chandra, Suman; Lata, Hemant; Radwan, Mohamed M.; ElSohly, Mahmoud A. (Planta Medica, 2018)
Cannabis (Cannabis sativa L.) is an annual herbaceous plant that belongs to the family Cannabaceae. Trans-Δ9-tetrahydrocannabinol (Δ9-THC) and cannabidiol (CBD) are the two major phytocannabinoids accounting for over 40% of the cannabis plant extracts, depending on the variety. At the University of Mississippi, different strains of C. sativa, with different concentration ratios of CBD and Δ9-THC, have been tissue cultured via micropropagation and cultivated. A GC-FID method has been developed and validated for the qualitative and quantitative analysis of acid and neutral cannabinoids in C. sativa extracts. The method involves trimethyl silyl derivatization of the extracts. These cannabinoids include tetrahydrocannabivarian, CBD, cannabichromene, trans-Δ8-tetrahydrocannabinol, Δ9-THC, cannabigerol, cannabinol, cannabidiolic acid, cannabigerolic acid, and Δ9-tetrahydrocannabinolic acid-A. The concentration-response relationship of the method indicated a linear relationship between the concentration and peak area ratio with R2 > 0.999 for all 10 cannabinoids. The precision and accuracy of the method were found to be ≤ 15% and ± 5%, respectively. The limit of detection range was 0.11 – 0.19 µg/mL, and the limit of quantitation was 0.34 – 0.56 µg/mL for all 10 cannabinoids. The developed method is simple, sensitive, reproducible, and suitable for the detection and quantitation of acidic and neutral cannabinoids in different extracts of cannabis varieties. The method was applied to the analysis of these cannabinoids in different parts of the micropropagated cannabis plants (buds, leaves, roots, and stems).
Keywords: Cannabis sativa L.; Cannabaceae; cannabinoids; GC-FID; TMS derivatization; quantitation